PERSEPSI PETANI TERHADAP KINERJA UED-SP DHARMA BAKTI DESA GABUNG MAKMUR KECAMATAN KERINCI KANAN KABUPATEN SIAK - Nazmi, Muhammad; Edwina, Susy; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to analyze the oil palm farmer perception of the performance UED-SP Dharma Bakti in Gabung Makmur Village Kerinci Kanan District of Siak Regency. This research was conducted in Gabung Makmur Village by purposive sampling method. Population in this research is the oil palm farmers in Gabung Makmur Village which is listed as a borrower of capital in UED-SP Dharma Bakti in 2013. The research objective is answered using a Likert's scale analysis methods Summated Rating (SLR). The results showed the perception of farmers on the performance UED-SP Dharma Bakti included in the category of "Good" seen from the organizational structure, work procedures, discipline, teamwork, and leadership. That can be seen from venture capital managers in providing a loan is easy, fast, and low interest rates.     Keywords: farmers, palm, perception, performance, UED-SP